2021
DOI: 10.1007/s10690-021-09351-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Performance of Islamic and Conventional Stock Indices: A Comparative Analysis

Abstract: Islamic indices encompass different fundamental principles to those held by conventional ones, which directs attention onto comparative financial performance. This paper offers a comprehensive performance comparison between Islamic indices and conventional indices, based on four main markets: worldwide, the US, Europe and Asia–Pacific for the period of 2007 and 2017 through financial ratio comparison and also the CAPM-EGARCH model. The main finding shows that Islamic indices yield higher average returns and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
(44 reference statements)
0
14
0
2
Order By: Relevance
“…Through the CAPM–GARCH model, Jawadi et al (2014) conclude that before the global financial crisis (GFC) of 2008, conventional indexes outperform Islamic indexes, whereas Islamic indexes outperform conventional indexes after the GFC of 2008. Asutay et al (2021), using the CAPM–EGARCH model, find that Islamic indexes outperformed conventional indexes during the GFC period and the post-crisis phase, particularly in the European and Asia–Pacific markets. Using the SD methodology, Al-Khazali et al (2014) compare conventional Dow Jones indexes to Islamic Dow Jones indexes.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Through the CAPM–GARCH model, Jawadi et al (2014) conclude that before the global financial crisis (GFC) of 2008, conventional indexes outperform Islamic indexes, whereas Islamic indexes outperform conventional indexes after the GFC of 2008. Asutay et al (2021), using the CAPM–EGARCH model, find that Islamic indexes outperformed conventional indexes during the GFC period and the post-crisis phase, particularly in the European and Asia–Pacific markets. Using the SD methodology, Al-Khazali et al (2014) compare conventional Dow Jones indexes to Islamic Dow Jones indexes.…”
Section: Literature Reviewmentioning
confidence: 97%
“…However, through CAPM statistics, Suryadi et al (2021) find that the JII has larger excess returns while having the same risk as compared to its conventional counterparts in Indonesia. Asutay et al (2021), using the CAPM–EGARCH model, undertake performance comparison between Islamic and conventional indices based on four main markets: worldwide, the USA, Europe and Asia–Pacific. Their finding shows that Islamic indexes yield higher average returns and lower risks in comparison to conventional indexes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abdelsalam et al (2014b) concluded that the SRI funds outperform Islamic funds in comparison. In a recent study carried out by Asutay et al (2021), a comparison is made between performance of Islamic and conventional indices of the USA, Asia-Pacific, European and other worldwide markets during the period 2007 and 2019. The study reveals that the Islamic indices outperformed conventional indices during 2007–2009; however; the results remained inconclusive during 2009–2013 whereby only in European and Asia-Pacific markets, the Islamic indices showed better performance compared to conventional indices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research from Ali et al (2022) and Jawadi et al (2019) stated that Islamic stocks are more stable and can survive better than conventional stocks during economic outbreaks. Research from Asutay et al (2022) and Majid (2018) also showed that Islamic stock outperformed conventional during the global financial crisis period (2007)(2008)(2009).…”
Section: Introductionmentioning
confidence: 99%